INCIDENTAL EXPOSURE AND L3 LEARNING OF MORPHOSYNTAX. Issue 4 (4th February 2014) - Grey, Sarah; Williams, John N.; Rebuschat, Patrick
Abstract : Evidence of learning following incidental exposure has been found for aspects of nonnative syntax in adults (Rebuschat & Williams, 2006, 2012 ; Williams & Kuribara, 2008 ). However, little research has tested delayed effects of learning under an incidental condition or moved beyond word order. This study investigated learning of third language (L3) morphosyntax (word order and case marking) under an incidental exposure condition. Participants were second language Spanish learners exposed auditorily to a semiartificial language, Japlish, during a semantic plausibility judgment task. Performance following exposure to L3 Japlish was assessed with acceptability judgment and picture-matching tasks that were administered immediately after exposure and 2 weeks later. Results on immediate tests showed a significant learning effect on acceptability judgment but none for picture matching. At delayed testing, results showed maintenance of the learning effect on acceptability judgment and significantly improved performance on picture matching. Results additionally showed that many of the learners arrived at the correct Japlish word-order rule; fewer did so for case marking. Follow-up analyses indicated that this rule knowledge, as measured by debriefing information, was important for performance on both assessment tasks, particularly at delayed testing. The results suggest that learning of L3 structures can take place following incidental exposure, that such learning is durable and undergoes improvement, and that development of reportable rule knowledge may also play an important role.